Calcium signaling of primary chondrocytes and ATDC5 chondrogenic cells under osmotic stress and mechanical stimulation. (December 2022) - Li, Wen; Zhou, Yilu; Han, Lin; Wang, Liyun; Lucas Lu, X.
Abstract: Calcium signaling plays an essential role in chondrocyte mechanotransduction. Guilak and colleagues have revealed the roles of TRPV4 and Piezo channels in chondrocyte calcium signaling and metabolism. This study compared the calcium responses of primary chondrocytes and ATDC5 cells induced by two different stimuli: osmotic stress and intense mechanical stimulus. Roles of three essential calcium signaling pathways, including extracellular calcium source, intracellular ER calcium store and mechanical-sensitive ion channels, were also investigated and compared between cells. Primary chondrocytes showed more vigorous calcium peaks under osmotic stress than under mechanical stimuli, while an opposite trend was found for ATDC5 cells. Extracellular calcium source, intracellular ER store, and PLC/IP3 pathway each played significant roles in the calcium responses of ATDC5 cells under both osmotic and mechanical stimuli. However, high level shear stress can directly cause ER release in primary cells without the presence of extracellular Ca 2+ or involvement of PLC-IP3 pathway. TRPV4 channel is essential for the responses of ATDC5 cells, but not for primary chondrocytes. In contrast, inhibition of mechano-sensitive channels had no significant effects on the ATDC5 cells. Therefore, primary chondrocytes and ATDC5 cells rely on distinct calcium sources and ion channels to initiate intracellular calcium signaling. Together, these results contribute to our understanding of stimulation-induced calcium signaling in primary chondrocytes and ATDC5 cells, and the different roles of three essential pathways between the two cell types.